Analysis of College Students’ Cybersecurity Awareness In Indonesia - Balqis Rofiqoh Chasanah; Candiwan Candiwan (Soegijapranata Catholic University, 2020)
Internet-based attacks have become common and are expected to happen continuously with the development of technology. Therefore, cybersecurity emerged as an important concept in everyday life. It is defined as the protection of cyberspace. Cybersecurity Awareness (CSA) exists as a major defense key in protecting users and systems from internet-based attacks. The research presented in this study aims to assess the level of CSA among college students in Indonesia. This study uses the Analytic Hierarchy Process (AHP) method to test students in three dimensions, including attitudes, knowledge, and behavior. To measure this dimension, six focus areas in the topic of cybersecurity were taken and developed from previous studies on the same topic. The six focus areas are password security, cyberbullying, phishing, malware, identity theft, and the last is downloading, sharing and use of pirated content. The results showed that the total level of CSA for college students in Indonesia was in the good criteria. This is indicated by a total percentage of awareness around 80%. Nevertheless there are some focus areas that can be improved to increase the percentage.